1998
DOI: 10.1116/1.581510
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of nickel sulfide catalysts

Abstract: Nickel sulfide catalysts obtained by homogeneous precipitation were prepared by varying the homogenization time and the sulfiding temperature. Structural characterization studies by transmission electron microscopy and x-ray diffraction showed the formation of various metastable crystalline phases at low temperatures of sulfiding (Ni3S2, Ni3S4, Ni7S6, Ni9S8, NiS2, NiS1.03, NiS), depending on the preparation conditions. NiS millerite appears to be the main phase for samples obtained after 4 h homogenization, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
27
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 11 publications
5
27
0
Order By: Relevance
“…It is a p-type semiconductor with a narrow band gap (0.5 eV) finds applications in cathode materials for rechargeable lithium batteries [6], catalysts [7,8], IR detectors [9], and sensors [10] as well as photoelectrochemical and solar cells [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It is a p-type semiconductor with a narrow band gap (0.5 eV) finds applications in cathode materials for rechargeable lithium batteries [6], catalysts [7,8], IR detectors [9], and sensors [10] as well as photoelectrochemical and solar cells [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Here in we synthesized pyrrole based nickel dithiocarbamate complexes, which are designed to coordinate anions via their pyrrole NH groups, precluding direct metal in coordination to the deprotonated pyrrole nitrogen atom. [9][10][11][12][13] Nickel sulfides posses electronic, 14 electrical magnetic 15 and optical properties 16 and can be used in various fields such as cathode materials in rechargeable lithium batteries, 17 catalysts for hydride nitrogen and hydro desulfurization 18,19 and IR detectors. [6][7][8] Nickel sulfides can form various compositions such as NiS, Ni 3+x S 2 , Ni 3 S 2 , Ni 7 S 6 , Ni 9 S 8 , Ni 3 S 4 , NiS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[12±19] Kosmac et al [12] reported a novel method for producing Ni 3 S 2 and NiS phases by mechanical alloying of Ni and S powders in a hardened stainless-steel vial in a glove box. Homogeneous precipitation by reaction between nickel nitrate and ammonium sulfide solutions at 80 C followed by heat treatment at 100 C in a mixture of 20 % H 2 S and 80 % H 2 showed a few broad reflections corresponding to the Ni 3 S 4 phase, [13] which decomposes to well-crystallized NiS 1.03 and NiS (millerite) phase on heat treatment at 200 C in a mixture of 20 % H 2 S and 80 % H 2 . Metastable Ni 3 S 4 single phase was obtained recently by an ambient temperature reaction between aqueous NiCl 2 and Na 2 S 2 O 4 solutions.…”
mentioning
confidence: 99%